2006
DOI: 10.1039/b513588e
|View full text |Cite
|
Sign up to set email alerts
|

Pressure induced phase transitions of TTAB-micellar solutions studied by SANS and Raman spectroscopy

Abstract: Using small angle neutron scattering in combination with optical Raman spectroscopy, phase transitions in the micellar system tetradecyl-trimethylammonium bromide (TTAB) have been investigated in a wide range of temperatures, pressures and surfactant concentrations. Allowing for the sluggish kinetics of crystallisation, the phase diagram in the p-T-c space could be determined that is dominated by a pronounced two-phase region of coexisting liquid and solid phases at elevated pressures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 16 publications
1
26
0
Order By: Relevance
“…One has noted that even binary surfactant/water systems have complex phase behavior. These self-assembled structures of surfactants in solutions can be controlled by tuning the related parameters such as temperature [2,3], pressure [4,5], ionic strength (the addition of salts) [6,7], nature of the counterions [8], the composites [9] and structures of surfactants [10]. Among the self-assembled aggregates formed by surfactants or their mixtures in solutions, vesicles which are more turbid than the L 1 -phase (micelles), optically isotropic and no long range order have attracted great attention because of their applications or potential applications in selective membranes, drug delivery, microreactors, and cosmetic applications [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…One has noted that even binary surfactant/water systems have complex phase behavior. These self-assembled structures of surfactants in solutions can be controlled by tuning the related parameters such as temperature [2,3], pressure [4,5], ionic strength (the addition of salts) [6,7], nature of the counterions [8], the composites [9] and structures of surfactants [10]. Among the self-assembled aggregates formed by surfactants or their mixtures in solutions, vesicles which are more turbid than the L 1 -phase (micelles), optically isotropic and no long range order have attracted great attention because of their applications or potential applications in selective membranes, drug delivery, microreactors, and cosmetic applications [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…4 shows a sequence of optical spectra obtained in the frequency regime of CH 3 /CH 2 -bending vibrations. The crystallization is associated with a pronounced narrowing of the vibrational lines along with an increase of the trans-conformers as shown by Haramagatti et al [3]. During the transition that occurs on a time scale of hours, a broad and unstructured spectrum is observed that might correspond to a gel-like intermediate state.…”
Section: Resultsmentioning
confidence: 82%
“…It is shown that the pressure-induced transition appears at the same values of pressure and temperature as the crystallization on cooling. Moreover, a thermal hysteresis of about 8 K or 400 bar is observed just as in the case of salt-free solutions [3].…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations